Synthesis of Branched‐Chain Sugars with a DHAP‐Dependent Aldolase: Ketones are Electrophile Substrates of Rhamnulose‐1‐phosphate Aldolases. Issue 19 (30th March 2018) - Laurent, Victor; Darii, Ekaterina; Aujon, Angelina; Debacker, Marine; Petit, Jean‐Louis; Hélaine, Virgil; Liptaj, Tibor; Breza, Martin; Mariage, Aline; Nauton, Lionel; Traïkia, Mounir; Salanoubat, Marcel; et al.
Abstract: Dihydroxyacetone phosphate (DHAP)‐dependent rhamnulose aldolases display an unprecedented versatility for ketones as electrophile substrates. We selected and characterized a rhamnulose aldolase from Bacteroides thetaiotaomicron (RhuABthet) to provide a proof of concept. DHAP was added as a nucleophile to several α‐hydroxylated ketones used as electrophiles. This aldol addition was stereoselective and produced branched‐chain monosaccharide adducts with a tertiary alcohol moiety. Several aldols were readily obtained in good to excellent yields (from 76 to 95 %). These results contradict the general view that aldehydes are the only electrophile substrates for DHAP‐dependent aldolases and provide a new C−C bond‐forming enzyme for stereoselective synthesis of tertiary alcohols. Abstract : Worth a try : Dihydroxyacetone phosphate (DHAP)‐dependent rhamnulose aldolases were found to show an unexpected tolerance for ketones as electrophile substrates, giving rise to branched‐chain monosaccharides with a tertiary alcohol moiety in good yields. These results contradict the accepted view that the aldehydes are the unique electrophile substrates of DHAP‐dependent aldolases.